Lobachevsky University: On the Way to Be a Research Leader - Editorial Article (Высшее образование в России, 2016)
Lobachevsky State University of Nizhni Novgorod celebrates centenary. In his interview with the Editor, the Rector of the University E.V. Chuprunov sums up its main achievements. During all its history, the University solved the tasks that were set by the Government and responded to challenges of society, particularly, the faculties of radiophysics, physics and higher school of general and applied physics prepared specialists for the defense industry. Today the University is the participant of the Programme 5-100. The priority research area at the University is biomedicine and neurosciences promoting the formation of the biggest biomedical cluster in Russia. The new quality of research is provided by high-capacity supercomputer "Lobachevsky" using supercomputing technologies. The latest project that had won the state grant is connected with launching of the software package "Cyberheart".